Subacute compartment syndrome in case of gunshot injuries of the extremities - Strafun, Sergiy; Laksha, Andriy; Shipunov, Volodymyr; Borzykh, Natalia; Strafun, Oleksandr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2024)
A local hypertensive ischemic syndrome or compartment syndrome (CS) is a serious complication of gunshot injuries of the extremities (GIE), it is usually considered as an acute process. However, we have repeatedly observed patients with subacute course of this pathology. Objective: to study cases of subacute CS (SaCS) with GIE, that are characterized by a latent course and veiled clinical picture of the complications. Methods: there were 15 cases of subacute CS after gunshot injuries for the period 2014–2018. 9 (60 %) were combined injuries of trunk and limbs, 6 (40%) — isolated limb wounds. Lesions of the lower extremities predominated — 10 (66.6 %). In 8 (53.3 %) patients, SaCS developed after shrapnel wounds of the limbs, and in 5 (33.3 %) cases — mine-explosive. Results: in 9 (60 %) cases, SaCS was observed in the bone-fascial sheath of the damaged area of the limb, in 6 (40 %) — in the adjacent segment. In 10 (66.6 %) patients, the course of SaCS was preceded by major vessels injury, in 8 (53.3 %) cases — it was combined with peripheral nerves injuries. In 12 wounded at the stages of evacuation, a tourniquet was used for more than an hour. In 5 cases, the course of SaCS was observed in patients with a combined wound of two or more anatomical sites with the development of a shock or prolonged hypotension. The time from the moment of injury to secondary surgical treatment, when the morphological signs of existed local hypertensive ischemic syndrome in bone-fascial sheath were identified, was from 5 days to 3 weeks. Conclusions: CS in case of GIE can have both acute and subacute flow patterns. SaCS usually develops in the intact segment of the injured limb without pronounced clinical manifestations. Risk factors for the course of SaCS: injuries of the main vessels, tourniquet for more than an hour, multilevel injuries with the development of a shock or prolonged hypotension, incomplete (untimely) fasciotomy at the evacuation stages.